Evaluating Compliance of Preoperative Investigations with National Institute for Clinical Excellence Testing Guidelines for Patients undergoing Elective Surgery: An Observational Study - Rahul Kurra; Lavanya Kaparti; T Sumanth; M Ravi (Journal of Clinical and Diagnostic Research, 2023)
Introduction: All patients posted for surgery are subjected to a series of tests. Recent studies have shown that many of these tests may not be necessary as they do not alter the anaesthetic technique. There are many international guidelines for ordering preoperative investigations. Aim: To determine the proportion of patients who underwent compliant testing and to identify the most common investigations which were not compliant with National Institute for Health and Care Excellence (NICE) guidelines. Materials and Methods: The study was a prospective observational study conducted on all patients undergoing elective surgery at Sri Devaraj Urs Medical College and RL Jalappa hospital, Kolar, Karnataka, India, from May 2022 to July 2022. The grade of surgery and the American Society of Anaesthesiologists (ASA) Physical Status of the patients was noted. The compliance of the tests with NICE guidelines was noted. Results: The preoperative investigations were done in 60 adult patients undergoing elective surgery. Renal function tests were the tests which were the most non compliant (60%) as per NICE guidelines. ECHO, Thyroid function tests and ECG were compliant in 78.3%, 91.7% and 60% of the patients, respectively. Conclusion: The tests which were most non compliant were coagulation profile and renal function tests. Further studies have to be done to check compliance with our Indian guidelines.